A tradition older than a country: IFK and the Sweden-inspired sports movement in Finland - Herd, K. (Soccer & Society, 2023)
This article presents several sport clubs in Finland connected to an organization Idrottsförening Kamraterna (Sporting Society Comrades), also known as IFK that originated in Sweden in 1895. The idea of IFK clubs reached Finland in 1897 and spread throughout the country. The beginning of the twentieth century was a period of growth and expansion for IFK, both in Sweden and Finland. IFK clubs formed an important network of sport-based activities, including football, when Finland was still a part of the former Russian empire. The aim of the article is to analyse how the modern Finnish IFKs from four different locations (Mariehamn, Åbo, Helsingfors and Grankulla) can retrace and frame their past.